2023
DOI: 10.3389/fcell.2023.1268565
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage and repair: underlying mechanisms leading to microcephaly

Jessica Honorato Ribeiro,
Nazlican Altinisik,
Nicholas Rajan
et al.

Abstract: DNA-damaging agents and endogenous DNA damage constantly harm genome integrity. Under genotoxic stress conditions, the DNA damage response (DDR) machinery is crucial in repairing lesions and preventing mutations in the basic structure of the DNA. Different repair pathways are implicated in the resolution of such lesions. For instance, the non-homologous DNA end joining and homologous recombination pathways are central cellular mechanisms by which eukaryotic cells maintain genome integrity. However, defects in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 279 publications
0
7
0
Order By: Relevance
“…IR causes DNA damage which normally induces a DDR (8). To investigate the activation of radiation-induced DNA damage in forebrain organoids, immunostainings were conducted for phosphorylated histone H2AX (ɣH2AX) and p53-binding protein 1 (53BP1), which both localize to DNA double-strand breaks (DSBs).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…IR causes DNA damage which normally induces a DDR (8). To investigate the activation of radiation-induced DNA damage in forebrain organoids, immunostainings were conducted for phosphorylated histone H2AX (ɣH2AX) and p53-binding protein 1 (53BP1), which both localize to DNA double-strand breaks (DSBs).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we analyzed gene expression profiles of the 30 known MCPH genes (6,8,9) in our organoids, both during their development and after irradiation. We found that the majority of MCPH-associated genes were significantly downregulated during organoid maturation, with the biggest changes occurring between D28 and D56 (Figure 6C).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations